Cores caiçaras : memórias, consumos e afetos compartilhados no litoral norte de São Paulo - Pedroza, Gilson Dias (2017)
This study examines photographs, mainly analogue ones, taken by the photographer Nícia Guerriero between the years of 1980 and 1990, which were then digitized and 20 years later posted on Facebook, via a virtual album on the photographer’s personal profile. These photos were taken on the north coast of São Paulo, São Sebastião, especially on the beach of Boiçucanga and its surroundings. Many of these images, which were mainly produced in order to document the Caiçara culture and the local landscape, became postcards or were featured in books. This research focus on the scanned images of the analogue photographs, that were later shared on Facebook. Its theoretical object relates to a symbolic consumption and emotional ties generated by the fact that they have gone through a few communication means, such as postcards, books and the internet. On the other hand, the empirical object refers to the virtual album named Cores Caiçaras. The overall objective is to investigate if such images have generated shared memories and interests. And the specific objective is to analyse images that portray a sense of community and if the interaction present on the social networking site can somehow recover, establish or promote some kind of recollecting memory and symbolic consumption, mostly on the emotional side. What we question is whether these digitally reproduced images and symbolically consumed on the social media could collaborate to strengthening the relations of the researched group as well as emanate individual and collective memories through the Cores Caiçaras Album. Our corpus brings observations about the produced material, including information on the facebook interactive tools such as like, share and more importantly comment as well as interviews with the protographer. The main authors that were invited to participate in our research are: Norval Baitello, Rose Rocha, Maurice Halbwachs, Joan Fontcuberta, Fausto Colombo, Boris Kossoy, Mônica Nunes. The results show that these photographs, most of which were taken around 30 years ago and that have been made public on the internet can bring back collective memories and feelings.